Bio-activation and mathematical modeling of ZIF-L encapsulated with laccase for enhanced ibuprofen removal from wastewater - Ayat Hassan; Shadi W. Hasan; Bart Van der Bruggen; Sulaiman Al-Zuhair (Cleaner Engineering and Technology)
This work explores the bio-activation of zeolitic imidazolate framework (ZIF-L) by laccase encapsulation for enhanced performance of emerging pollutant removal from wastewater. ZIF-L exhibits high surface area, porosity, and selective adsorption characteristics, which contribute to its effective adsorption of ibuprofen. Under the same conditions, the ibuprofen removal increased from 50% using bare ZIF-L to 83% using bio-activated ZIF-L. The Kinetics and thermodynamics of ibuprofen adsorption on ZIF-L were studied and mathematically modeled. The effect of laccase encapsulation inside the ZIF-L crystals was thoroughly investigated using a diffusion-reaction model, which was solved numerically using a finite difference explicit scheme. The results showed deep ibuprofen penetration within the ZIF-L crystal containing encapsulated laccase. The bio-activated ZIF-L was used in a fixed-bed column to study the continuous removal of ibuprofen. The dynamic behavior of the continuous fixed-bed system was mathematically modeled to predict the concentration profiles and breakthrough curves at various initial ibuprofen concentrations. This study presents a novel approach demonstrating the positive effect of laccase catalytic activity in enhancing the performance of ZIF-L as an adsorbent for ibuprofen removal. The approach offers an effective, economical, and environmentally friendly method to remove emerging pollutants from wastewater.